SAFE SLEEP: A MODERN LOOK AT INSOMNIA MEDICATIONS FOR SENIORS - Katarzyna Krupa; Katarzyna Kozon; Małgorzata Krzyżanowska; Patrycja Fiertek; Hanna Krupa; Weronika Głowacz; Zuzanna Mioduchowska; Anna Pietrzak; Zofia Szypuła; Zuzanna Burkacka (International Journal of Innovative Technologies in Social Science, 2025)
Background. Insomnia is a common and burdensome condition in older adults, marked by difficulty falling or staying asleep, early awakenings, and non-restorative sleep. Its prevalence increases with age and is linked to cognitive decline, depression, falls, and reduced quality of life. Physiological aging and polypharmacy complicate treatment in this group.Aim. This paper reviews current pharmacological options for managing insomnia in the geriatric population, focusing on efficacy, safety, and adherence to clinical guidelines.Materials and Methods. A literature review was conducted using PubMed, Scopus, and Google Scholar. Sources included randomized controlled trials, systematic reviews, meta-analyses, observational studies, and guidelines published up to 2024. Keywords included “insomnia,” “elderly,” “pharmacological treatment,” “hypnotics,” and related terms. Only studies involving patients aged 65+ were analyzed. Data on efficacy, safety, dosing, duration, and guideline recommendations were extracted.Analysis of Literature. Current guidelines prioritize non-pharmacological treatments. Pharmacotherapy may be considered when behavioral methods are ineffective or unavailable. Prolonged-release melatonin and low-dose doxepin offer the best safety-efficacy balance. Orexin receptor antagonists show promise but are not yet available in Poland. Sedating antidepressants like trazodone, mirtazapine, and mianserin may be cautiously used in patients with comorbid depression or anxiety. Z-drugs and benzodiazepines, despite their efficacy, pose significant risks such as falls, dependence, and cognitive decline. Antihistamines and antipsychotics are generally not recommended due to unfavorable safety profiles.Conclusion. Pharmacological treatment of insomnia in older adults should be cautious and individualized. Non-drug therapies remain the first-line option. When medications are necessary, the safest agents should be used at the lowest effective doses for the shortest duration. Ongoing research is essential to expand safe therapeutic options.